High-accuracy discretization methods for solid mechanics (Archives of Mechanics - Test, 2003)
Novel high-accuracy computational techniques for solid mechanics problems are presented. They include fourth-order and arbitrary-order finite difference methods based on Pade-type differencing formulas and a meshless method which uses radial basis functions in a "finite difference" mode. Some results illustrating high performance of the suggested numerical methods are displayed.